2019
DOI: 10.1038/s41385-018-0053-0
|View full text |Cite|
|
Sign up to set email alerts
|

Interbacterial mechanisms of colonization resistance and the strategies pathogens use to overcome them

Abstract: The communities of bacteria that reside in the intestinal tract are in constant competition within this dynamic and densely colonized environment. At homeostasis, the equilibrium that exists between these species and strains is shaped by their metabolism and also by pathways of active antagonism, which drive competition with related and unrelated strains. Importantly, these normal activities contribute to colonization resistance by the healthy microbiota, which includes the ability to prevent the expansion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
183
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(192 citation statements)
references
References 169 publications
(195 reference statements)
4
183
0
5
Order By: Relevance
“…Experimental studies have shown beneficial effects of a bacteriocin produced by probiotic strains of C. butyricum in preventing infection in other Clostridia, including Clostridium difficile [55] and Clostridium pasteurianum [56], yet its effect on C. botulinum remains to be investigated. Additional mechanisms for competitive microbial resistance may include nutrient limitation, enhancing the intestinal mucosal barrier, and activation of host immunity [57].…”
Section: The Possible Role Of the Gut Microbiome In Colonizationmentioning
confidence: 99%
“…Experimental studies have shown beneficial effects of a bacteriocin produced by probiotic strains of C. butyricum in preventing infection in other Clostridia, including Clostridium difficile [55] and Clostridium pasteurianum [56], yet its effect on C. botulinum remains to be investigated. Additional mechanisms for competitive microbial resistance may include nutrient limitation, enhancing the intestinal mucosal barrier, and activation of host immunity [57].…”
Section: The Possible Role Of the Gut Microbiome In Colonizationmentioning
confidence: 99%
“…Colonisation resistance occurs through an array of direct or indirect bacterial and host interactions including competition for nutrients, host metabolites and physical space 10 . An example of nutrient competition is the commensal Bacteroides thetaiotaomicron which consumes carbohydrates essential to murine pathogen Citrobacter rodentium causing it to be excluded 11 .…”
Section: Introductionmentioning
confidence: 99%
“…56 Establishment of these key pathogens in murine guts has been linked to antibiotic-induced decrease in anaerobic flora. 14,[21][22][23][50][51][52][53]57 ESBL K. pneumoniae colonization has been associated with piperacillin-tazobactam, ceftriaxone, and ceftazidime when administered in large doses. 29 We know that the invading E. coli and K. pneumoniae strains used in our study do not persist in healthy murine guts without antibiotic pressure (controls here and 34 ), indicating that their persistence was a direct consequence of dysbiosis.…”
Section: Discussionmentioning
confidence: 99%